(untitled) (Bangladesh Journal of Neuroscience, 2014)
Background: The diagnosis of ischemic stroke remains a clinical one, with confirmatory evidence obtained through neuroimaging. ECG changes are common in patients with ischemic stroke. Objective: The objective of this study was to see ECG findings among ischemic stroke patients. Materials and Methods: This study was carried out in the Department of Neurology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka from July 2006 to October 2008. A total of 36 patients with acute Ischemic stroke were selected by purposive sampling method and diagnosed by history, clinical findings ard was confirmed by CT scan of head. The clinical details, investigations of the respondents were reviewed. Data were recorded in a pre-designed data collection sheet. Result: Majority of the subjects were in 7th decade 12(33.3%) and 6th decade 9(25%) with the male to female ratio was 1.25:1. Among the patients with abnormal electrocardiographic findings, 7(19.4%) patients each had myocardial ischemia, 4(11.1%) had conduction block and ventricular arrhythmias, 7(19.4%) had atrial fibrillation, 5(13.9%) had ventricular hypertrophy, 7(19.4%) had myocardial infarction, 6(16.7%) patients had non-specific ST changes. Conclusion: Myocardial ischemia, atrial fibrillation and myocardial infarction are common electrocardiographic findings of ischemic stroke patients. Bangladesh Journal of Neuroscience 2014; Vol. 30 (1): 23-26